2018
DOI: 10.1148/rg.2018170046
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Pulmonary Hypertension: From CT to Clinical Diagnosis

Abstract: Pulmonary hypertension (PH) is a condition characterized by increased pressure in the pulmonary circulation. It may be idiopathic or arise in the setting of other clinical conditions. Patients with PH tend to present with nonspecific cardiovascular or respiratory symptoms. The clinical classification of PH was recently revised at the World Health Organization symposium in Nice, France, in 2013. That consensus statement provided an updated classification based on the shared hemodynamic characteristics and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 67 publications
0
28
0
1
Order By: Relevance
“…A number of pathological entities exhibit bronchial artery enlargement on CTA, including cystic fibrosis, post infectious bronchiectasis, and chronic pulmonary embolus, that later of which is also associated with SAPAF (8). In our case, we excluded these pathological processes from our differential diagnosis based on the patient's clinical history and predominate HRCT finding of emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…A number of pathological entities exhibit bronchial artery enlargement on CTA, including cystic fibrosis, post infectious bronchiectasis, and chronic pulmonary embolus, that later of which is also associated with SAPAF (8). In our case, we excluded these pathological processes from our differential diagnosis based on the patient's clinical history and predominate HRCT finding of emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…However, one study reported prevalence of Type 1 (85%) and Type 2 pulmonary vascular abnormalities (15%) in cirrhosis patients with HPS [13]. Interestingly, several authors have cited and referenced these data, extrapolating the values to CT imaging [11, 12]. However, this prevalence was established with conventional pulmonary angiography among just 7 patients and performed by one observer [13].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some authors [11,12] have extrapolated to CT data from a pulmonary angiographic study of just 7 patients [13], which classified patterns of pulmonary vascular abnormalities as type 1 (distal vascular dilatation with multiple vessels extending toward the pleura and subpleural space) and type 2 (arteriovenous malformations and nodular dilatations of the peripheral vessels). However, no previous studies have addressed the prevalence of these two patterns of pulmonary vascular abnormalities in a larger sample of patients with HPS or evaluated the reproducibility of CT pulmonary vasculature and bronchial-to-artery ratio measurements in such patients.…”
Section: Introductionmentioning
confidence: 99%
“…The webs and occlusions appear different to acute pulmonary emboli and can be easily overlooked. In CTED there is no pulmonary hypertension and the generic features of pulmonary hypertension may be absent, but the webs and occlusions are present 4 5…”
Section: Discussionmentioning
confidence: 99%